Basic Variables of Economic and Social Development in Balkan Region (Regional Development -Industrialisation-Humanpower) - Yozgat, Fazil (European Journal of Sustainable Development, 2014)
In this study, three subjects had been investigated. Firstly history of industry Balkan region, secondly basic variables economic and social development, thirdly relation to variables. Industry is basic element of development. In addition to in this paper theoretical and literal concept has been investigated. In this study is aimed at presenting the most important new trends of economic, social, political and institutional development of Balkan region with relation to four major factors shaping the regions countries. Industrial Revolution in Europe and made major investments in the first half of the 19th century particularly central Europe and Balkan region. Balkan regions represent complex and diverse reality. These regions are from Old Continent to Central Europe, South East Europe and Mediterranean. From Adriatic to Black Sea and Mediterranean also. In these regions there are some different economic, social and political events. I.e. Croatia moves to final round member of European Union some countries face to particular problems of political subjects. I offer framework analysis of the regional country by country based on the existing set of criteria, which are variables of social and economic development. Those variables are including (cluster industry, expenditure R&D od GDP, variations of capitals, population and market, some trade block which are impact of economic and social development) Proposed key pillars to support sustainable competitiveness in the Western Balkans. Sustaining competitiveness =Human capital development==Regional Cluster==Sector Policy reforms.(OECD,2008) Key words. Balkan region, Social development, Globalisation, Sustainable development